2021
DOI: 10.3389/fcimb.2021.686004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Induced by TgMIC5 and TgMIC16 DNA Vaccines Against Toxoplasmosis

Abstract: Toxoplasma gondii is an obligate intracellular parasite, which is responsible for a widely distributed zoonosis. Effective vaccines against toxoplasmosis are necessary to protect the public health. The aim of this study is to evaluate the immune efficacy of DNA vaccines encoding TgMIC5 and TgMIC16 genes against T. gondii infection. The recombinant plasmid pVAX-MIC5 and pVAX-MIC16 were constructed and injected intramuscularly in mice. The specific immune responses and protection against challenge with T. gondii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…A previous study showed that vaccination with pVAX-MIC16 or pVAX-MIC5 induces T lymphocyte proliferation. In this study, immunization with pVAX-MIC16, pVAX-MIC5 or pVAX-MIC16 + pVAX-MIC15 significantly increased the percentage of CD4 + and CD8 + T cells compared with the control group (Zhu et al, 2021). Furthermore, the proportion of CD4 + and CD8 + T lymphocytes significantly increased in mice vaccinated with the TG290 mRNA-LNP vaccine, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study showed that vaccination with pVAX-MIC16 or pVAX-MIC5 induces T lymphocyte proliferation. In this study, immunization with pVAX-MIC16, pVAX-MIC5 or pVAX-MIC16 + pVAX-MIC15 significantly increased the percentage of CD4 + and CD8 + T cells compared with the control group (Zhu et al, 2021). Furthermore, the proportion of CD4 + and CD8 + T lymphocytes significantly increased in mice vaccinated with the TG290 mRNA-LNP vaccine, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…We found that all immunized mice induced significant T. gondii specific splenocyte cell proliferation, suggesting that an adaptive immune response to parasite infection was activated, which may contribute to an effective cellular immune response. 28 the single protein group, the survival time of the rTgBAG1-rTgROP8 group was increased, the brain cysts were reduced, and the humoral and cellular immune responses were enhanced. By further analysis of the ratio of IgG1 to IgG2a of the two IgG subtypes, it was found that the IgG2a level induced by the rTgBAG1 group was higher than that of IgG1, causing the immune response of Th2 type bias.…”
Section: Discussionmentioning
confidence: 97%
“…Largemouth bass injected with LMBV DNA vaccine encoding major capsid protein (MCP) also showed an up‐regulation of IL‐8 (Jia et al, 2020). Zhu et al (2021) found that IL‐12p40 expression was remarkably increased after DNA vaccine immunization in mice. These immune‐related gene upregulations further indicate that pcDNA3.1‐G plasmids induce a strong immune response after immunization of largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been found in other studies:Zhao et al (2019) found that IL-8 was upregulated in subunit vaccine. Largemouth bass injected with LMBV DNA vaccine encoding major capsid protein (MCP) also showed an up-regulation of IL-8(Jia et al, 2020) Zhu et al (2021). found that IL-12p40 expression was remarkably increased after DNA vaccine immunization in mice.…”
mentioning
confidence: 97%